Communication or promotion? The role of communication practitioners in CSR - Eiró-Gomes, Mafalda (2019)
Corporate Social Responsibility (CSR), or maybe we should already be speaking about sustainability, are some of those concepts that belonging to the realm of organizations have different definitions, interpretations and are given different levels of importance according to the size, the sector or just the interest of those in charge. What seems to be common to all these organizations is that communication practitioners are those responsible for its promotion. The question that the authors will be discussing here goes, however, beyond this idea. Is communication seen as a constitutive function in organizations? Do portuguese organizations belonging to GRACE (an association of institutions concerned with CSR) see the communication practitioners as mere promoters of the organization CSR activities or do they have strategic responsibilities in the CSR definitions and programmes? In the framework of an interpretivist paradigm, a sequential explanatory mixed methods approach was developed. This method is a two phase design that is characterized by an initial quantitative phase of data collection and analysis, followed by a phase of qualitative one. An invitation to answer an online survey was sent to all the 158 organizations. Afterwards face-to-face interviews with the CSR responsible were conducted to those organisations that answered the survey. The qualitative results were used to explain and enable researchers to interpret the results from the quantitative approach. According to the first results communication seems to be understood in these organizations just as a way to reach certain publics and not as a constitutive and strategic function regarding CSR.